Increased sanitization potency of hydrogen peroxide with synergistic O3 and intense pulsed light for non-woven polypropylene. Issue 39 (7th July 2021) - Jeong, Robin; Kumar, Hitendra; Jones, Steven; Sandwell, Allen; Kim, Keekyoung; Park, Simon S.
Abstract : By introducing synergistic elements to the VHP processes, potent sanitization of polymeric filters is achieved at low H2 O2 concentrations. Abstract : Supplies of respiratory masks have recently become a concern due to the onset of the SARS-CoV-2 pandemic. Sanitization and reuse of masks can alleviate high mask consumption and production stresses. In the present work, improved sanitization potency of vaporous hydrogen peroxide (VHP) treatment of resilient bacterial spores while retaining polymeric filter performance was explored. A batch fumigation chamber with hydrogen peroxide (H2 O2 ) vapor and ozone (O3 ) is featured, followed by intense pulsed light (IPL) flash treatments. A resilient bacterial indicator, Geobacillus stearothermophilus ( G. stearothermophilus ), was utilized to compare the efficacy of various H2 O2 concentrations in combination with O3 and IPL. It was found that exposure to 30 minutes of 4.01 L min −1 0.03% H2 O2 aqueous vapor and 3 g h −1 O3 followed by 10 IPL flashes per side completely inactivated G. stearothermophilus . The xenon sourced IPL irradiation was found to synergistically enhance radical production and strengthen the complementary biocidal interaction of H2 O2 with O3 . Due to the synergistic effects, H2 O2 was able to sanitize at a diluted concentration of 0.03% H2 O2 . The physical properties, such as surface potential, tensile strength, hydrophobicity, and filtration efficiency of >300 nm saline water aerosol of fibrous polypropylene (PP) sheets, were maintained. In addition, no residue of sanitizers was detected, thus confirming the biosafety and applicability of this method to disposable masks. Performance was benchmarked and compared with commercially available processes. The synergistic regime was found to achieve sterilization of G. stearothermophilus at drastically reduced H2 O2 concentrations and in ambient conditions relative to commercial methods.